Expressions of Tourism and Local Economic Development in Progreso Restaurants - Ávila Aguilar, Andrés Joel; Garcilazo Ortiz, Ángel Adolfo (HITOS DE CIENCIAS ECONÓMICO ADMINISTRATIVAS, 2023)
OBJECTIVE: To know the economic impact generated by tourism in the State of Yucatan, mainly in the Port of Progreso, this is due to its great contribution to the Gross Domestic Product, therefore, it seeks to identify elements of local economic development to provide opportunities for improvement in restaurants in Progreso, Yucatan.MATERIAL AND METHOD: It will be used the quantitative research, focused on a series of scientific precision techniques and cross-sectional research, that is, the study will only be carried out in a certain period to analyze and collect data that will be used in the documentation.RESULTS: Histograms and Pearson correlations were obtained, in which we can highlight the following points: there is a relationship between tourism and the promotion of new strategies, there is also a relationship between culinary activities and business promotion.CONCLUSION: It is considered to implement strategies focused on tourism and, above all, to promote the Port of Progreso, Yucatán, highlighting its culture, through local actors, especially in the business field.
Keywords: Economic development; Restaurants; Tourism.